Hayk Nahapet – Epic Hero and Cosmic God - Vardumyan, G.
The Armenian historical tradition has preserved evidence about the eponymous ancestors Hayk and Aram, who gave their names to the country and the nation. The most ancient narratives are about Hayk Nahapet (Patriarch) – the epic hero of the Armenian nation after whom Armenians call themselves Hay and their country Hayk’ (Hayq). The legends also mention Aram, a heroic figure of the sixth generation of Hayk, whose name gave rise to the exonyms Armenia and Armenians. These patriarchs symbolize Armenian national identity and have been deified for centuries. Both eponyms, Hayk and Aram, are mentioned in various written sources. This article traces the evolution of Hayk’s image – from a brave giant-hunter to an epic archer, and from a patriarch-ancestor to a cosmic god-creator personifying time and eternity. For thousands of years, Hayk has remained the central figure in the ethnogonic myths of the Armenian nation. His multi-layered figure has played an epoch-making role in the processes of the formation and development of Hayk’-Armenia, ensuring its endurance through millennia and its continuation into the present day.
Keywords: Philology